ANALISIS AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN KEUANGAN PADA KANTOR CAMAT LAIS KABUPATEN MUSI BANYUASIN - Ahmad Irfansyah; Candra Romanda; Rano Asoka (Institut Rahmaniyah Sekayu, 2023)
This study aims to analyze the extent of accountability and transparency in financial management applied at the Lais Sub-District Office, Musi Banyuasin Regency. The data used in this study were data of the 2019-2021 fiscal year. The data collection technique used were interviews, conducted with the heads of sub-heads and staff of the planning, finance and reporting sections related to the financial management of the Lais Sub-District Office, and documentation of financial documents, such as reports Realization of Implementation of Lais Sub-District Office Development Activities in 2019-2021. The results obtained showed that the management of regional finances in the Lais District Office of Musi Banyusin Regency overall could be categorized as accountable and transparent. It could be seen that the Lais sub-district office had been able to fulfill all accountability and transparency indicators that the financial management of the Lais Sub Ddistrict Office was all good.